A history of Chinese global Internet governance and its relations with ITU and ICANN. Issue 1 (2nd January 2020) - Negro, Gianluigi
Abstract : The Chinese contribution to global Internet governance debate has been studied mainly by focusing on the governmental perspective. This study was aimed to provide a broader view by analyzing the participation of Chinese academics and civil society in two of the most important Internet governance international organizations: the Internet Corporation for Assigned Names and Numbers (ICANN) and the International Telecommunication Union (ITU). Based on historical material and in-depth interviews conducted in Geneva and Beijing, the findings show the evolution of Chinese Internet governance at the global level and suggest the following: first, the Chinese agents in the global debate on Internet governance support a multi-stakeholder perspective; second, although seldom engaged in the decision-making process, the Chinese agents involved in the global governance identify ITU as the more credible international organization in coordinating global governance; third, the Chinese agents have an ambivalent approach to Chinese participation both in ITU and ICANN. Finally, the findings of the study reported in this article contest the understanding that Chinese Internet governance is isolationist in nature.